Taking care of Terrific - Lowry, Lois. (Boston : Houghton Mifflin, 1983)
Taking her overprotected young charge to the public park to broaden his horizons, fourteen-year-old baby sitter Enid enjoys unexpected friendships with a black saxophonist and a bag lady until she is charged with kidnapping.
Booklist.
School Library Journal.
Wilson's Junior High School.
6.7
6.7
5-8.
Keywords: Babysitters -- Fiction; Parks -- Fiction; Babysitters -- Fiction; Parks -- Fiction; Boston (Mass.) -- Fiction; Boston (Mass.) -- Fiction